Factors influencing commitment: the bisexual husband's perspective in Malaysian marital relationships - Mohd Rafizey Dalin,; Nur Hafizah Yusoff,; Azlina Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Commitment is crucial in a marriage to ensure that the relationship can endure and thrive. This includes mixed orientation marriages where one partner is a bisexual male, and the other is a heterosexual spouse. In a conservative country like Malaysia, socio-cultural and religious influences undoubtedly exert significant pressure and affect the ability and commitment of bisexual husbands to remain in their marriages, often necessitating the concealment of their sexual identity from their partners. This study aims to identify the factors influencing the commitment levels of bisexual husbands to their marital relationships. Using a qualitative research approach, in-depth interviews were conducted with 15 bisexual husbands who are currently married. The findings revealed that love for their wives, caring for their children, hope for change, internal religious motivation, upholding family honor, and avoiding social stigma are key elements contributing to maintaining commitment in their marriages. The insights gained from this study are expected to guide the development of interventions, support programs, and more effective counseling, as well as the formulation of more inclusive and supportive policies for this group within the context of marriage. Additionally, this study aims to raise societal awareness about the challenges faced by bisexual males in maintaining their marriages, thereby helping to reduce stigma and discrimination.